Abnormal FDG Biodistribution in a Patient With Gitelman Syndrome. (May 2021) - Yamamoto, Yuka; Mitamura, Katsuya; Norikane, Takashi; Fujimoto, Kengo; Takami, Yasukage; Nishiyama, Yoshihiro
Abstract : Abstract: Gitelman syndrome is an autosomal recessive renal tubulopathy. A 38-year-old woman was diagnosed with Gitelman syndrome. Eight years later, 18 F-FDG PET/CT was performed to evaluate recurrence of endometrial cancer. FDG PET images showed an extremely abnormal FDG biodistribution. They showed decreased brain uptake, increased cardiac muscle uptake, and diffuse increased muscle and adipose tissue uptake. This pattern is similar to high insulin state; however, her glucose level was normal, and insulin level was very low.